Influence of thiourea on the corrosion resistance of mild steel immersed in simulated concrete pore solution - Krishnasamy Vigneswari; Karunaivel Kavipriya; Brintha Arockiasamy Santhiya; Veerapandian Velkannan; Gurmeet Singh; Hashem Abdulhameed Al; Anitha Nilavan; Susai Rajendran; Časlav Lačnjevac (Zaštita Materijala)
The corrosion resistance of mild steel in simulated concrete pore solution (SCPS) in the absence and presence of thiourea has been investigated by polarization study and AC impedance spectra. Polarisation study reveals that thiourea system functions as anodic inhibitor. AC impedance spectra reveal that a protective film is formed on the metal surface. When mild steel is used as rebar, thiourea may be mixed with concrete. Thus the mild steel will be protected from corrosion. The protective film consists of iron-thiourea complex formed on metal surface. In the presence of thiourea the linear polarisation resistance increases, corrosion current decreases, charge transfer resistance (Rt) increases, impedance increases, phase angle increases and double layer capacitance (Cdl) value decreases. This formulation may find application in concrete technology.